Efektivitas Roadmap Program Corporate Social Responsibility pada IPC II (Indonesia Port Corporation) tahun 2018 - 2020 - Helvivi Anggriyani; Intan Fitri Meutia; Devi Yulianti (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2021)
Corporate Social Responsibility is an obligation carried out by the company and regulated in article 74 paragraph (1) of Law No. 40 of 2007 on Limited Liability Companies. Social responsibility carried out by IPC is realized through the IPC Peduli program. The purpose of this research is to find out the effect of roadmap csr programs on IPC II.. The method used in this research is a type of descriptive study with a qualitative approach. Data collection is conducted using observation techniques, interviews and documentation. The results showed that there are three areas of programs that become the main focus of CSR in IPC, namely in the field of environment, education and health. The effectiveness of the roadmap CSR programs at IPC can be shown that the implementation is considered quite effective on several indicators such as target accuracy, goal achievement and real change indicators. Indicators whose implementation is not optimal are focused on understanding related to CSR programs. The peoples around the portof panjang has not fully understand every CSR programs in IPC due to the lack of socialization carried out by the IPC to the community, and the lack of timeliness in the implementation of activities in the environmental and health fields. In the implementation of CSR programs there are inhibitory factors and supporting factors from internal and external aspects.